PERENCANAAN TURN PAD 01 DENGAN FLEXIBLE PAVEMENT DI BANDAR UDARA KALIMARAU - Bambang Wasito; Agung Dwi Laksono; Cahyaning Setyarini (Approach : Jurnal Teknologi Penerbangan, 2019)
The Kalimarau Berau Airport – East Borneo is an airport which is established under the airport operational unit located near the city,located ARP Latitude 02 09’00’’ N Longitude 117 26’ 00’’ E with its own dimension runway 2250 m x 45 m.The Kalimarau Berau airport has its own location indicator WAQT and its function is providing air transportation services.Therefore, it’s important to provide the best service for the flight operation.Especially able to accommodate the Boeing 737-800.Due to traffic that Kalimarau had, unwanted things often happen. The refinement of runway often happens which is causing delay on exisisting flight. One wheel lock, which is the aircraft had to rotate by locking one of its own wheel is the causing of the refinement of the runway.It’s also happened because of the absence of the turn pad at Kalimarau Berau’s runway. The purpose of this writings is to make a plan for establishing turn pad area 01 with flexible pavement. The method used for the pavement based from INternational civil aviation organization (icao) and federal avition administra(faa) which is manualy calculated (by graphic) and using FAARFIELD. And for the calculation of PCN is using COMFAA.